2018
DOI: 10.1093/labmed/lmy036
|View full text |Cite
|
Sign up to set email alerts
|

The Use and Misuse of Statistical Methods in Cytopathology Studies: Review of 6 Journals

Abstract: Our assessment of use of statistical methods in this subsection of pathology demonstrated a need for improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…19 but after that and in current times, statistical errors in medical journals are no less than before. [20][21][22][23][24][25]…”
Section: Statistical Errors In Medical Journalsmentioning
confidence: 99%
“…19 but after that and in current times, statistical errors in medical journals are no less than before. [20][21][22][23][24][25]…”
Section: Statistical Errors In Medical Journalsmentioning
confidence: 99%
“…A recent study has empirically evaluated statistical quality in diagnostic pathology research [20]. Bahar et al found the majority of cytopathology studies examined were retrospective, and statistical errors and omissions were common.…”
Section: Discipline-specific Vulnerability To False Positivesmentioning
confidence: 99%
“…For instance, Diong, Butler, Gandevia, and Heroux (2018) reported that in spite of published editorial advice, poor data analysis and statistical reporting are still common in published research papers. Furthermore, Bahar, Pambuccian, Barkan, and Akdas (2019) reviewed six cytopathology journals and found that only about 50% of original articles were free of statistical errors.…”
mentioning
confidence: 99%